Group Counseling Using Islamic Stress Management to Reduce Parenting Stress - Rahma, Rahma; Patera Adwiko Priambodo; Ernita Armelia; Sani Nuramalia (Universitas Islam Negeri Raden Intan Lampung, 2026)
Parenting stress among mothers of young children is a significant mental health concern in Indonesia, particularly in the post-COVID-19 pandemic period, with negative implications for parenting quality and child development. Within a predominantly Muslim society, a stress management approach grounded in Islamic values may have potential effectiveness. This study aimed to examine the effectiveness of Islamic Stress Management (ISM) group counseling in reducing parenting stress among mothers of young children. The study employed a quasi-experimental design with pre-test, post-test, and follow-up assessments involving seven mothers of young children in Yogyakarta. The intervention consisted of eight weekly group counseling sessions integrating ISM strategies (tawakkul, patience, gratitude, and dhikr) with supportive group dynamics. Parenting stress data were analyzed using paired-samples t-tests following the Shapiro–Wilk normality test. The results showed significant reductions in stress scores between the pre-test and post-test (t(6) = −5.261, p = 0.002), pre-test and follow-up (t(6) = −6.301, p = 0.001), and post-test and follow-up (t(6) = −5.461, p = 0.002), indicating sustained intervention effects. These findings suggest that ISM group counseling not only effectively reduces parenting stress but may also produce substantial effects at follow-up. The findings provide preliminary evidence for the development of evidence-based Islamic psychology interventions for Indonesian Muslim mothers, with practical implications for counseling services in community health centers (Puskesmas), early childhood education institutions, and religious organizations. Keywords: group counseling, Islamic stress management, parenting stress